Implementation of an anti-flu vaccination campaign in a hospital pharmacy service - Eva Fernández-Cañabate; Virginia Martínez-Santana (Elsevier, 2020)
Objective: To determine the impact of the implementation of an influenza vaccination campaign in a hospital pharmacy service on patients who are starting or receiving treatment with biological therapies. Method: A 15-month quasi-experimental study of patients starting or receiving treatment with biological therapies. Between October and December 2016 and October and December 2017, we compared influenza vaccination rates, the incidence of influenza in the study population, the direct impact of the vaccination campaign on the patient, the effect of the campaign on vaccination rates, and the results of the satisfaction survey. Results: A total of 188 patients participated in the study. Of the patients who had not been vaccinated in the 2016/2017 campaign, 72.6% were vaccinated (p < 0.000) during the 2017/2018 campaign. No statistically significant differences were found between the 2016/2017 and 2017/2018 campaign (p = 0.636) in the percentage of patients who contracted flu after receiving the vaccine. In total, 99.5% thought that the campaign was a good initiative, and 50.5% reported that their decision to be vaccinated was influenced by the fact that the campaign was led by the hospital pharmacy service. Conclusions: The implementation of the influenza vaccination campaign in the hospital pharmacy service achieved led to a marked increase in vaccination rates. This result underlines the key role played by the hospital pharmacy service in achieving this level of success.